(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The aim of study was to estimate resource funds of common reed and response of reed stands to harvesting in the Central Ukraine, within the national nature park “Pyriatynskyi”, and uncover possibilities and consequences of regular reed harvesting for rehabilitation and sustainable management practice of floodplain in the park. By sampling three large sites of reeds differed by duration of flooding we estimated morphometric values, above-ground airdried biomass of reed and some rates of plant resource capacity. Results show that annual accumulation of reed biomass reaches low to upper medium values (2–17 t*ha.-1) known in temperate Europe. To conserve wetlands, to keep the floodplain and natural habitats in stable ecological mode the conditions of reed harvesting are recommended. Admissible rates of utilization of common reed through winter harvesting were stated. Based on indicator values obtained on sample plots an expected yield was predicted. There was confirmed no significant response of reed stands to winter harvesting in the first growing year after harvesting.